Adaptive Potential of Adults with Attention Deficit/Hyperactivity Disorder (ADHD) - Hrys , Antonina; Chepeleva , Nataliia; Tkachuk , Tetiana; Tor , Larysa (Insight: the psychological dimensions of society, 2024)
The aim was a theoretical-empirical study of the adaptive potential of adults with attention deficit/hyperactivity disorder (ADHD). Methods. The sample consisted of adults with ADHD, totaling n = 32, of which n = 16 were female (50.00%) and n = 16 were male (50.00%). The participants’ ages ranged from 20 to 54 years (M = 36.12; Me = 36.00; SD = ± 8.43). A theoretical-empirical complex of methods was used, which included theoretical methods: retrospective analysis, synthesis, comparison, and generalization, as well as empirical methods: “The Work and Social Adjustment Scale” (W&SAS) (Mundt et al., 2002); “Zung Self-Rating Depression Scale” (ZSDS) (Zung, 1965); “Impact of Even Scale – Revised” (IES-R) (Sveen et al., 2010); “Generalized Anxiety Disorder Assessment Scale” (GAD-7) (Spitzer et al., 2006; adapted by N. Aleksina et al., 2024) and “New Methodology for Diagnosing Psychosocial Maladjustment” (NDMPM) (Herasymenko, 2018). Results and discussion. It was established that the parameter “work” has statistically significant correlations with depressiveness, anxiety disorders, and types of responses to traumatic events (p < .001). It was noted that the area where participants feel most comfortable is “personal leisure”, which is associated with the protective response of avoidance and anxiety disorders. It was argued that avoidance, as a defense mechanism and type of response to a traumatic event, only increases the tendency towards isolation and distancing. It was suggested that a constructive organization of the workspace for individuals with ADHD would enhance their adaptive capacity. Conclusions. The study of the adaptive potential of adults with ADHD revealed significant patterns of work and social adaptation among the participants. It was summarized that acceptance and support from the environment are crucial; tolerance and the absence of stigma within the family, workplace, and society at large had a positive effect; isolation is partly accompanied by a lack of support, which can lead to severe manifestations of ADHD and comorbid disorders; the impact of traumatic events was reflected in the mental states of the participants.